1999
DOI: 10.1074/jbc.274.31.21995
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phospholipase C δ1 through C2 Domain by a Ca2+-Enzyme-Phosphatidylserine Ternary Complex

Abstract: The concentration of free Ca 2؉ and the composition of nonsubstrate phospholipids profoundly affect the activity of phospholipase C ␦1 (PLC␦1). The rate of PLC␦1 hydrolysis of phosphatidylinositol 4,5-bisphosphate was stimulated 20-fold by phosphatidylserine (PS), 4-fold by phosphatidic acid (PA), and not at all by phosphatidylethanolamine or phosphatidylcholine (PC). PS reduced the Ca 2؉ concentration required for half-maximal activation of PLC␦1 from 5.4 to 0.5 M. Approximately 12 distinct isoforms of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…Although suppression of these binding sites does not impair the ability of PLC-δ1 to hydrolyze PI(4,5) P 2 [47]. It has been shown that PLC-δ1 exhibits a specific Ca 2+ -dependant binding to PEcontaining membranes through its C2 domain [48]. Since the C2 domain is almost integrated with the Y region, it is thought to assist in orienting the catalytic site of PLC-δ1 onto the membrane once bound through initial association by the PH domain (i.e.…”
Section: C2 Domain and C-terminal Extensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although suppression of these binding sites does not impair the ability of PLC-δ1 to hydrolyze PI(4,5) P 2 [47]. It has been shown that PLC-δ1 exhibits a specific Ca 2+ -dependant binding to PEcontaining membranes through its C2 domain [48]. Since the C2 domain is almost integrated with the Y region, it is thought to assist in orienting the catalytic site of PLC-δ1 onto the membrane once bound through initial association by the PH domain (i.e.…”
Section: C2 Domain and C-terminal Extensionmentioning
confidence: 99%
“…This peptide was therefore defined as the signal transfer region of Gβ. Extensive studies with other peptides identified a second signal transfer region (Gβ [42][43][44][45][46][47][48][49][50][51][52][53][54] ) in the seventh blade of Gβ, and revealed segments in the second, fifth and seventh blade that hold the Gβγ/PLC-β2 complex together during activation ( Figure 5) [67,68]. In addition, it was found that the geranylgeranylated moiety attached to the C-terminal segment of the Gγ, which is proximal to the membrane and anchors Gβγ to lipids, binds to the PLC-β2 [69,70].…”
Section: Plc-β2 Binding Site(s) In Gβγmentioning
confidence: 99%
See 2 more Smart Citations
“…Most Ca 2ϩ -dependent membrane binding C2 domains have higher affinity for anionic membranes than for zwitterionic ones. In particular, the C2 domains of PKC-␣ (PKC-␣-C2) and phospholipase C-␦1 show selectivity for phosphatidylserine (PS) (15)(16)(17). In contrast, the C2 domains of group IVa cytosolic phospholipase A 2 (cPLA 2 ) (18) and 5-lipoxygenase (19) strongly favor zwitterionic phosphatidylcholine (PC).…”
mentioning
confidence: 99%